Preclinical evaluation of a plant-derived SARS-CoV-2 subunit vaccine: Protective efficacy, immunogenicity, safety, and toxicity. Issue 32 (30th July 2022) - Shanmugaraj, Balamurugan; Khorattanakulchai, Narach; Panapitakkul, Chalisa; Malla, Ashwini; Im-erbsin, Rawiwan; Inthawong, Manutsanun; Sunyakumthorn, Piyanate; Hunsawong, Taweewun; Klungthong, Chonticha; Reed, Matthew C.; Kemthong, Taratorn; Suttisan, Nutchanat; et al.
Highlights: Efficacy, safety and toxicity of Baiya SARS-CoV-2 Vax 1 was tested in animal models. Baiya SARS-CoV-2 Vax 1 provided protection against SARS-CoV-2 challenge. The vaccine elicits effective humoral immune response. The vaccine is safe, immunogenic and tolerated without any adverse or toxic effects. Abstract: Coronavirus disease 2019 (COVID-19) is an acute respiratory illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The prevention of SARS-CoV-2 transmission has become a global priority. Previously, we showed that a protein subunit vaccine that was developed based on the fusion of the SARS-CoV-2 receptor-binding domain (RBD) to the Fc portion of human IgG1 (RBD-Fc), produced in Nicotiana benthamiana, and adjuvanted with alum, namely, Baiya SARS-CoV-2 Vax 1, induced potent immunological responses in both mice and cynomolgus monkeys. Hence, this study evaluated the protective efficacy, safety, and toxicity of Baiya SARS-CoV-2 Vax 1 in K18-hACE2 mice, monkeys and Wistar rats. Two doses of vaccine were administered three weeks apart on Days 0 and 21. The administration of the vaccine to K18-hACE2 mice reduced viral loads in the lungs and brains of the vaccinated animals and protected the mice against challenge with SARS-CoV-2. In monkeys, the results of safety pharmacology tests, general clinical observations, and a core battery of studies of three vital systems, namely, the central nervous, cardiovascular, and respiratory systems, did not reveal any safety concerns. The toxicology study of the vaccine in rats showed no vaccine-related pathological changes, and all the animals remained healthy under the conditions of this study. Furthermore, the vaccine did not cause any abnormal toxicity in rats and was clinically tolerated even at the highest tested concentration. In addition, general health status, body temperature, local toxicity at the administration site, hematology, and blood chemistry parameters were also monitored. Overall, this work presents the results of the first systematic study of the safety profile of a plant-derived vaccine, Baiya SARS-CoV-2 Vax 1; this approach can be considered a viable strategy for the development of vaccines against COVID-19.